Phytochemical Investigation of Fruits of Corylus colurna Linn. - Prashad Sharma3, Humaira Farooqi4, and Hamid Nawaz Khan2*, Parwaiz Akhtar1, Mohd Ali2, Maheesh (Journal of Phytology, 2010)
Four chemical constituents, steroidal glycosides, namely colurnasterol glycoside, b-sitosterol glycoside, campesteryl glycoside and corylusterol glycoside (new compound) have been isolated from the fruits of Corylus colurna and their structures were established as 20-b-hydroxycampesterol-3b-D-glucopyranoside (F1), stigmast-5-en-3-O-b-D-glucopyranoside (F2), (24R)ergost-5-en-3b-D-glucopyranoside (F3) and cholest-5-en-3b, 12 b-triol-3b-D-glycopyranoside (F4) by spectral data analyses and chemical evidences. Key words: Steroidal glycosides, namely Colurnasterol glycoside, b-Sitosterol glycoside, Corylus colurna Linn. (Family: Betulaceae) <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Parwaiz Akhtar et al. Phytochemical Investigation of Fruits of Corylus colurna Linn. J Phytol 2/3 (2010) 89-100.